Flow Boiling of Water in a Rectangular Metallic Microchannel - ÖZDEMİR, MEHMED RAFET (TAYLOR & FRANCIS INC, 2021)
The article presents the experimental results of flow boiling of water in single rectangular microchannels. Three rectangular copper microchannels having the same hydraulic diameter (0.56 mm) and length (62 mm) but different aspect ratios (width/height, 0.5, 2.56, and 4.94) were investigated using de-ionized water as the working fluid. The experiments were conducted over the experimental range of mass flux 200-800 kg/(m(2)s), heat flux 4-1350 kW/m(2) and inlet subcooling of similar to 14 K. The results showed that the channel with smaller aspect ratio exhibited better heat transfer performance up to certain heat fluxes (similar to 480-500 kW/m(2)), whilst the effect of channel aspect ratio became insignificant for higher heat fluxes. The flow boiling patterns were observed and the main flow regimes were bubbly, slug, churn, and annular flow. Flow reversal was also observed that caused a periodic flow in the two microchannels having smaller aspect ratio. A comparison of the experimental results with widely used macro and micro-scale heat transfer correlations is presented. The macro-scale correlations failed to predict the experimental data while some micro-scale correlations could predict the data reasonably well.
Keywords: EVAPORATIVE HEAT-TRANSFER; 2-PHASE FLOW; PRESSURE-DROP; GENERAL CORRELATION; ASPECT RATIO; FLUX; MINICHANNELS; ORIENTATION; PERFORMANCE; PATTERNS